Analyzing policy change of Malawi ICT and Digitalization policy: Policy Assemblage Perspective - Frank Makoza (ZBW - Leibniz Information Centre for Economics, 2023)
The Government of Malawi set out to implement national ICT policy from 2013 to 2016. The policy activities were partially executed, and recently reviewed the ICT policy to incorporate digitization. This paper reviewed policy change that led to the development of Malawi ICT and digitalization. Using Deleuze and Guattari's Assemblage Theory, the study analysed policy documents and media reports. Content analysis was used to analyse the secondary data. The findings showed that the policy development activities departed from the conventional process of policy cycle championed in the line ministry of the ICT sector. Instead, the Presidential Delivery Unit coordinated the policy change. The process destabilized policy activities to address service delivery, transformation of economic sectors and created opportunities for policy actors to exercise their distributed agency. The study contributes to the literature on policy change of national digital policies in the context of developing countries.
Keywords: 330; Policy change; Policy Assemblage; National Digital policy; Digitalization policy; Malawi